Survey on industrial big data - Jianmin WANG (大数据, 2017)
Industrial big data is a collection of data in the industry application,which consist of business data in the information system,machine data in the industrial IoT system,and related data in the related websites.Industrial big data is a very important component of industrial internet.The main resources of the industrial big data were analyzed with introduction of the industrial internet.Then the relationships among “industrial big data,enterprise digitalization and industrial internet” were discussed.The“multi-typed,high-throughput,and strong-correlated” characteristics of industrial big data were presented.A typical industrial big data application scenario with “cross-time-scale,cross-supply-chain,and cross-organization” was shown.Furthermore,Industrial big data software architecture was discussed and a real-life application case was shown.